Implementation of ESG in the Agricultural Sector to Support Sustainable Agriculture in Indonesia - Ummul Hikmah Saragih (Journal of Economics, Management, Development, and Education, 2026)
This study aims to analyze the application of the Environmental, Social, and Governance (ESG) concept in the agricultural sector to support sustainable agriculture in Indonesia. The research is motivated by the increasing challenges in the agricultural sector such as climate change, environmental degradation, low farmer welfare, and weak agricultural governance that impact the sustainability of the national agricultural sector. The ESG concept is presented as a sustainable development approach that emphasizes the balance between environmental, social, and governance aspects in agricultural activities. The research method used is qualitative research with a descriptive approach. Data analysis techniques use the interactive model of Miles, Huberman, and Saldaña which includes data reduction, data presentation, and extraction. The results of the study indicate that the application of ESG in the agricultural sector in Indonesia has a significant influence in supporting sustainable agriculture. The environmental aspect influences natural resource management, environmental conservation, and reducing the negative impacts of agricultural activities on the ecosystem. The social aspect influences the improvement of farmer welfare and empowerment through training, institutional strengthening, and social protection. Meanwhile, the governance aspect influences transparency, accountability, and the effectiveness of agricultural sector governance. However, ESG implementation still faces various obstacles such as low farmer literacy, limited access to technology and financing, and suboptimal government policy support.